The ichnofamily Celliformidae for celliforma and allied ichnogenera - Genise, Jorge Fernando (2000)
This contribution undertakes a comprehensive revision, lacking until now, of all the ichnotaxa attributed to fossil bee cells, one of the most common traces in paleosols. These ichnotaxa are morphologically related to Celliforma and consequently grouped herein in the new ichnofamily Celliformidae. Two new ichnogenera are formulated, Cellicalichnus igen, nov., for several ichnospecies previously included in Celliforma, and a new ichnospecies, C. chubutensis isp. nov., belonging to this ichnofamily, and Brownichnus igen. nov., for the ichnospecies favosites, which is not morphologically related to Celliforma. The ichnogenera included in this ichnofamily involve traces in which Celliforma, the most simple trace of the group, is part of their structure. Palmiraichnus is akin to Celliforma with antechambers and discrete walls. Uruguay, Corimbatichnus and Rosellichnus are clusters composed of adjacent rows of Celliforma, or Palmiraichnus-like cells. Ellipsoideichnus and Cellicalichnus are different arrangements of Celliforma-like cells attached to tunnels. Celliformidae are based on the morphology of the traces, all of them comprising cells, groups of cells and cells attached to tunnels. As such, its component ichnotaxa are based exclusively on morphological ichnotaxobases, which, in turn, were evaluated and selected with respect to the nest architecture of the trace makers, the bees. This paper analyzes some procedures and clues (i.e. behavioral homologies) that may be used to select the proper taxobases to erect ichnotaxa when the identity of the trace makers is known, as in this study case.